Atrial Myocyte NLRP3/CaMKII Nexus Forms a Substrate for Postoperative Atrial Fibrillation. Issue 8 (25th September 2020) - Heijman, Jordi; Muna, Azinwi Phina; Veleva, Tina; Molina, Cristina E.; Sutanto, Henry; Tekook, Marcel; Wang, Qiongling; Abu-Taha, Issam H.; Gorka, Marcel; Künzel, Stephan; El-Armouche, Ali; Reichenspurner, Hermann; et al.
Abstract : Rationale: Postoperative atrial fibrillation (POAF) is a common and troublesome complication of cardiac surgery. POAF is generally believed to occur when postoperative triggers act on a preexisting vulnerable substrate, but the underlying cellular and molecular mechanisms are largely unknown. Objective: To identify cellular POAF mechanisms in right atrial samples from patients without a history of atrial fibrillation undergoing open-heart surgery. Methods and Results: Multicellular action potentials, membrane ion-currents (perforated patch-clamp), or simultaneous membrane-current (ruptured patch-clamp) and [Ca 2+ ]i -recordings in atrial cardiomyocytes, along with protein-expression levels in tissue homogenates or cardiomyocytes, were assessed in 265 atrial samples from patients without or with POAF. No indices of electrical, profibrotic, or connexin remodeling were noted in POAF, but Ca 2+ -transient amplitude was smaller, although spontaneous sarcoplasmic reticulum (SR) Ca 2+ -release events and L-type Ca 2+ -current alternans occurred more frequently. CaMKII (Ca 2+ /calmodulin-dependent protein kinase-II) protein-expression, CaMKII-dependent phosphorylation of the cardiac RyR2 (ryanodine-receptor channel type-2), and RyR2 single-channel open-probability were significantly increased in POAF. SR Ca 2+ -content was unchanged in POAF despite greater SR Ca 2+ -leak, with a trend towards increased SR Ca 2+ -ATPase activity. Patients with POAF also showed stronger expression of activated components of the NLRP3 (NACHT, LRR, and PYD domains-containing protein-3)-inflammasome system in atrial whole-tissue homogenates and cardiomyocytes. Acute application of interleukin-1β caused NLRP3-signaling activation and CaMKII-dependent RyR2/phospholamban hyperphosphorylation in an immortalized mouse atrial cardiomyocyte cell-line (HL-1-cardiomyocytes) and enhanced spontaneous SR Ca 2+ -release events in both POAF cardiomyocytes and HL-1-cardiomyocytes. Computational modeling showed that RyR2 dysfunction and increased SR Ca 2+ -uptake are sufficient to reproduce the Ca 2+ -handling phenotype and indicated an increased risk of proarrhythmic delayed afterdepolarizations in POAF subjects in response to interleukin-1β. Conclusions: Preexisting Ca 2+ -handling abnormalities and activation of NLRP3-inflammasome/CaMKII signaling are evident in atrial cardiomyocytes from patients who subsequently develop POAF. These molecular substrates sensitize cardiomyocytes to spontaneous Ca 2+ -releases and arrhythmogenic afterdepolarizations, particularly upon exposure to inflammatory mediators. Our data reveal a potential cellular and molecular substrate for this important clinical problem. Abstract : Supplemental Digital Content is available in the text.